From Norvelt to nowhere - Gantos, Jack.; Gantos, Jack. (London : Corgi Yearling, 2013)
After an explosion, a new crime by an old murderer, and the sad passing of the founder of Norvelt, Pennsylvania, twelve-year-old Jack accompanies his slightly mental elderly mentor, Miss Volker, on a cross-country run as she pursues the oddest of outlaws.
6.5
5-8.
5-8
Keywords: Friendship -- Juvenile fiction; Old age -- Juvenile fiction; Friendship -- Fiction; Humorous stories; Mystery and detective stories; Old age -- Fiction; Friendship -- Fiction; Humorous fiction; Mystery fiction; Old age -- Fiction; Norvelt (Pa.) -- History -- 20th century -- Juvenile fiction; Norvelt (Pa.) -- History -- 20th century -- Fiction; Norvelt (Pa.) -- History -- Fiction; Humorous fiction; Mystery fiction